Expression and characterization of a two-component alkanesulfonate monooxygenase system from thermophilic bacterium Anoxybacillus geothermalis strain D9 - Yusoff, Durratul Fatini (2021)
The wide distribution of xenobiotic alkanesulfonate compounds in nature without proper handlings has raised health and environmental concerns. Degradation of these compounds happens naturally with the help of microorganisms. Alkanesulfonate monooxygenase system from bacteria carries out biodegradation of alkanesulfonate molecule. It is a two-component enzyme system that involved flavin transfer between flavin mononucleotide (FMN) reductase (SsuE) and alkanesulfonate monooxygenase (SsuD). SsuE supplies reduced FMN (FMNH2) to SsuD as a cofactor. However, most alkanesulfonate monooxygenase systems studied were originated from mesophilic bacteria. Moreover, the stability and characteristic of the thermophile-origin alkanesulfonate monooxygenase system were unclear. Therefore, the expression and characterization of the thermophilic alkanesulfonate monooxygenase system can be applied for the bioremediation of xenobiotic alkanesulfonate pollutants. In this study, the properties of the recombinant alkanesulfonate monooxygenase system and its components from thermophilic Anoxybacillus geothermalis D9 were reported for the first time. The study aims to discover the biochemical and biophysical nature of SsuE and SsuD from thermophiles. In this study, ssuE and ssuD genes from A. geothermalis D9 were successfully cloned into an expression vector pET-51b (+) and expressed in Escherichia coli strain Rosetta (DE3). The recombinant SsuE and SsuD were purified via affinity chromatography with a molecular mass of 21.7 and 46.3 kDa, respectively. Temperature and thermal denaturation analysis show that SsuD with an optimum temperature of 40 °C is slightly more thermostable than SsuE that is optimal at wide range temperatures (30 – 50 °C). Their stability in a wide temperature ranging from 20 to 50 °C indicates that they are thermostable enzymes. Both proteins also prefer pH 8 but SsuD is more stable in slightly alkaline pH as compared to SsuE. Furthermore, the alkanesulfonate monooxygenase system in this study is stable in most organic solvents especially those with high LogP. This system catalyzed redox reactions, thus, their activities were greatly enhanced by the presence of most metal ions. These proteins are moderately stable in non-ionic surfactants and greatly inhibited by anionic surfactants. Physical and structural analysis of this system found that they are mainly made up of α-helices. Besides, in silico studies predict SsuE and SsuD exist as dimeric α/β/α flavodoxin and TIM barrel structure, respectively. The computational analysis also predicted the active pockets and interaction of protein residues with the substrate was located in the C-terminal end of β-sheets for both proteins. In general, SsuD characterized in this study exhibits better stability as compared to SsuE which might be due to the differences in their protein structure. In conclusion, the thermostable alkanesulfonate monooxygenase system from A. geothermalis D9 with a unique pH stability profile and active in many types of solvents making it an attractive multi-enzyme system to be exploited for bioremediation or industrial purposes.